Congenital mesoblastic nephroma: A case report and review of literature - Bwala KJ; Umar AM; Suleiman DE; Abdullahi I; Zaidu am; Mustapha SS; Adamu D; Habibu KA; Aliyu NS; Alhassan N (Ibom Medical Journal, 2025)
Introduction: Congenital mesoblastic nephroma is a rare renal tumour affecting newborns and infants. It is also known as leiomyomatous or fetal hamartoma and is the most common solid Renal tumor in the neonate and infants less than 6 months old.